Efektivitas Ekstrak Daun Beluntas (Pluchea Indica) Terhadap Mortalitas Ulat Kubis Plutella Xylostella - Yudo Sakti; Retno Wijayanti; Sholahuddin Sholahuddin (Agrotechnology Research Journal, 2018)
One type of vegetable products in Indonesia is cabbage. However, in the application of cultivating cabbage vegetables had experienced some problems, especially the crop caterpillar of Plutella xylostella. Pest control at the level of farmers in some areas, generally they still use chemical pesticides. As a solution for excessive use of chemical pesticides, the use of botanical insecticides is interesting to develop. One of the plant materials that is easily found in the surrounding environment is “beluntas” leaf (Pluchea indica L) containing alkaloids, flavonoids, saponnins, and tannins. The purpose of this study was to determine the effect of leaves extract of (P. indica) on caterpillar mortality of P. xylostella and the phytotoxicity effect on pakcoy. The results of the research showed that the extract wasn't sufficiently able to affect the larvae mortality of P. xylostella, The treatment concentration of 30% however was able to suppress the emergence of the imago. The extract did not show any phytotoxicity symptom the pakcoy .